Non-destructive geophysical-archaeological investigations of the site at Tablada de Lurin (Peru) - Misiewicz, Krzysztof; Makowski, Krzysztof (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2003)
The paper presents the results of resistivity surveying carried out in 2001-2002 at the Tablada de Lurin cemetery near Lima in Peru. The research was conducted in association with the Catholic Pontifical University in Lima as part of an intervention and conservation program. The chief objective was to identify the spatial extent of the burial ground and the location of concentrations of two main types of tombs occurring at this site: cist graves and shaft-and-chamber tombs. Geoelectric measurements covered an area of ca. 3 ha, using twin-probe and Wenner arrangements on a meter grid. A test was made of the usefulness of the magnetic method applied as gradient measurements taken with a proton magnetometer. The results provided the grounds for planning further archaeological excavations. Simultaneously, they served to record the actual condition of various features and the potential threats to the ancient substance
il. ; 24 cm